How digital technologies can support positive psychology - Barnes, Steven; Prescott, Julie (Positive psychology in practice, 2025)
There is an increasing prevalence and use of technology that extends into the support of mental health and wellbeing. How Digital Technologies can Support Positive Psychology focuses on how digital technologies can support mental health and wellbeing in the field of positive psychology. Introducing a number of digital innovations - such as artificial intelligence (AI), gamified solutions, wearable technologies, social media, and the use of remote data collection and analysis - Barnes and Prescott explore how these can support areas of positive psychology such as wellbeing, flow, resilience, relationships and improving quality of life. An instrumental volume linking the two areas of digital technologies and positive psychology, How Digital Technologies can Support Positive Psychology examines how specific applications of digital technologies may be effective in supporting specific aspects of positive psychology to boost mood and attain and maintain positive outcomes.